Ly6C- Monocytes Regulate Parasite-Induced Liver Inflammation by Inducing the Differentiation of Pathogenic Ly6C+ Monocytes into Macrophages. - Yannick Morias; Chloé Abels; Damya Laoui; Eva Van Overmeire; Martin Guilliams; Elio Schouppe; Frank Tacke; Carlie J deVries; Patrick De Baetselier; Alain Beschin (PLoS Pathogens, 2015)
Monocytes consist of two well-defined subsets, the Ly6C+ and Ly6C- monocytes. Both CD11b+ myeloid cells populations have been proposed to infiltrate tissues during inflammation. While infiltration of Ly6C+ monocytes is an established pathogenic factor during hepatic inflammation, the role of Ly6C- monocytes remains elusive. Mice suffering experimental African trypanosome infection die from systemic inflammatory response syndrome (SIRS) that is initiated by phagocytosis of parasites by liver myeloid cells and culminates in apoptosis/necrosis of liver myeloid and parenchymal cells that reduces host survival. C57BL/6 mice are considered as trypanotolerant to Trypanosoma congolense infection. We have reported that in these animals, IL-10, produced among others by myeloid cells, limits the liver damage caused by pathogenic TNF-producing Ly6C+ monocytes, ensuring prolonged survival. Here, the heterogeneity and dynamics of liver myeloid cells in T. congolense-infected C57/BL6 mice was further dissected. Moreover, the contribution of Ly6C- monocytes to trypanotolerance was investigated. By using FACS analysis and adoptive transfer experiments, we found that the accumulation of Ly6C- monocytes and macrophages in the liver of infected mice coincided with a drop in the pool of Ly6C+ monocytes. Pathogenic TNF mainly originated from Ly6C+ monocytes while Ly6C- monocytes and macrophages were major and equipotent sources of IL-10 within myeloid cells. Moreover, Nr4a1 (Nur77) transcription factor-dependent Ly6C- monocytes exhibited IL-10-dependent and cell contact-dependent regulatory properties contributing to trypanotolerance by suppressing the production of TNF by Ly6C+ monocytes and by promoting the differentiation of the latter cells into macrophages. Thus, Ly6C- monocytes can dampen liver damage caused by an extensive Ly6C+ monocyte-associated inflammatory immune response in T. congolense trypanotolerant animals. In a more general context, Ly6C- or Ly6C+ monocyte targeting may represent a therapeutic approach in liver pathogenicity induced by chronic infection.